rs1800890 Polymorphism of IL-10 and Susceptibility to Idiopathic Thrombocytopenic Purpura - Zeylabi, Fatemeh; Jalali, Mohammad Taha; Kaydani, Gholam-Abbas; Jaseb, Kaveh; Saki, Najmaldin (Journal of Pediatric Genetics, 2023)
Immune thrombocytopenic purpura (ITP) is an immune bleeding disorder that is reported in approximately 2 out of every 100,000 adults with a mean age of 50 years. Several factors such as various genetic backgrounds are associated with the pathogenesis of ITP. Interleukin (IL)-10 is a complicated cytokine that has a role in tumor progression, antitumor immunity, and immune system regulation. rs1800890 is an IL-10 single nucleotide polymorphism linked to lower levels of IL-10. A total of 67 patients with ITP and 70 healthy individuals (controls) were considered in this study. The IL-10 polymorphism was detected by the amplification refractory mutation system–polymerase chain reaction technique. According to our analysis, individual carriers of the AA genotype were less likely to develop ITP. The AT genotype was more common in patients with ITP in comparison to the control group. However, there was no significant association between rs1800890 genotypes (p = 0.775, odds ratio =1.517, 95%) in the acute and chronic groups. We observed that women had a higher mean frequency of this polymorphism (p = 0.0012). The rs1800890 AA genotype was associated with the highest platelet counts. However, the mean platelet volume and platelet distribution width values among alleles of the polymorphisms did not vary significantly. The IL-10 rs1800890 polymorphism may have a role in idiopathic thrombocytopenic purpura etiology. As a result, more research with a larger number of sample sizes is suggested.
Keywords: genotype; immune thrombocytopenic purpura; megakaryocyte; IL-10; platelet; polymorphism